Education, Social Mobility and Empowerment - Shankar L. Araballi, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Viksit Bharat @ 2047 is the Government of India’s vision to transform the country into a developed nation by its 100th year of Independence in 2047. The initiative focuses on achieving comprehensive and sustainable development through inclusive growth, innovation and good governance. In this direction, the Govt. of India invited ideas and suggestions from its citizens across India to throw light on this vision especially in the field of empowering youth, the poor, women and farmers with strategic priorities in areas like education, health care, infrastructure, and technology. Hence today’s National Seminar is also organized on the prime motive of gathering ideas to focus on the vision of Viksit Bharat. At this juncture, I chose a subtheme titled Education, Social Mobility and Empowerment, so that to provide insights on the above areas with regard to Viksit Bharat 2047. Education, Social Mobility and Empowerment all these three aspects are interrelated each other. A) Education: “Education is a process of gaining knowledge, Skills, & Art, so that to earn livelihood and to lead an independent life.” Hence, Education plays vital role in bringing social change not only at micro level, but also at macro level.B) Social Mobility: “Social Mobility is a movement of an individual and a social group from one social position to another.” Further Education is observed as one of the prominent factors of social mobility.C) Empowerment: “Empowerment is a process of obtaining Power, Right, and Capability of taking decisions and performing duties.” It signifies becoming Stronger, Self-Reliant, and capable of doing duties by gaining Knowledge, Skills and Resources. Education will be the strong foundation for Social Mobility & Empowerment for Viksit Bharat 2047 At outset, from various researches and studies it is strongly believed that, Education is the only means to advance and empower our nation economically, technologically, culturally, politically and socially as a whole. In this regard, various questions arise before us that, what kind of education we need. What will be our dimensions of Education? In this regard, I brought some suggestions, which could justify the objectives of today’s seminar topic. Let us look at a little glance on the dimensions of Education that could help to empower the people so that to empower the nation and thereby create social mobility in the life of the people of the nation.
Keywords: Skill based Education; Self-Job oriented Education; Vocational Training; Educational Outreach; Extension Education